Molecular Design of Ferrocene-Tyrosine Methacrylate Polymers for Enhanced Electrochemical Stability and Optoelectronic Device Applications - Aydin, Derya; AMIN, Murad Hiwa; Cetiner, Rumeysa; Akman, Feride; Koran, Kenan; Biryan, Fatih (Springer, 2026)
In this study, ferrocene-functionalized methacrylate polymer was synthesized and comprehensively characterized to explore its electrochemical stability, optical properties, and photodiode performance. The monomer (Mon-Tyr-Fc) was prepared by esterification of a ferrocene-tyrosine derivative with methacryloyl chloride, and subsequently polymerized via free radical polymerization (FRP) to yield the homopolymer P(Tyr-Fc). The HOMO-LUMO energy gaps of the Mon-Tyr-Fc and P(Tyr-Fc) calculated by the TD-DFT method. Fluorescence quantum yield measurements showed a strong solvent-dependent behavior in THF and DMSO. Electrochemical analysis via cyclic voltammetry indicated reversible redox behavior, where the anodic and cathodic peak currents varied linearly with scan rate, even at high scan speeds. To evaluate its optoelectronic performance, P(Tyr-Fc) was incorporated into a heterojunction device structure (Al/p-Si/P(Tyr-Fc)/Al). Moreover, under varying light intensities (20-100 mW/cm2), the reverse bias current increased proportionally, confirming its photosensitive behavior. The P(Tyr-Fc) polymer demonstrates a rare combination of redox reversibility, optical activity, and tailorable side-chain functionality, making it a strong candidate for next-generation applications in organic electronics, particularly in the development of organic photovoltaics, wearable sensors, and light-responsive optoelectronic devices such as photodiodes.
Keywords: Ferrocene; Polymer; Diode; Theoretical calculation; Electrochemical properties